2022
DOI: 10.1155/2022/5331712
|View full text |Cite
|
Sign up to set email alerts
|

OffFog: An Approach to Support the Definition of Offloading Policies on Fog Computing

Abstract: IoT devices deployed in Smart Cities usually have significant resource limitations. For this reason, offload tasks or data to other layers such as fog or cloud is regularly adopted to smooth out this issue. Although data offloading is a well-known aspect of fog computing, the specification of offloading policies is still an open issue due to the lack of clear guidelines. Therefore, we propose OffFog—an approach to guide the definition of data offloading policies in the context of fog computing. In order to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…We found that less energy consumption had scores of 55% based on the EEEF approach. Figure 3 displays the findings of the research that were compared with those of previously established method [21]- [25].…”
Section: Resultsmentioning
confidence: 99%
“…We found that less energy consumption had scores of 55% based on the EEEF approach. Figure 3 displays the findings of the research that were compared with those of previously established method [21]- [25].…”
Section: Resultsmentioning
confidence: 99%
“…The main objective is to offload the workload of cloud computing down to the edge of the network and perform some processing locally also rather than just passing the data to and from the cloud. Moreover, The survey paper also discuss about various healthcare architectures based on Fog computing, covering various features like security of patient data discussed by [10,11,12,13], response time for emergency cases discussed by [14,15,16,17,18], medical cost considered by [19] and [20] focus on management of medical data. The paper also compare Fog and Mist computing and discussed about a collaborative Cloud, Fog, Mist Healthcare architecture, deploying intelligence at various edge of the network for a better healthcare system.…”
Section: Introductionmentioning
confidence: 99%